2023
DOI: 10.1021/acschembio.3c00047
|View full text |Cite
|
Sign up to set email alerts
|

Key Amino Acid Residues of Mitochondrial Transcription Factor A Synergize with Abasic (AP) Site Dynamics To Facilitate AP-Lyase Reactions

Abstract: Human mitochondrial DNA (mtDNA) encodes 37 essential genes and plays a critical role in mitochondrial and cellular functions. mtDNA is susceptible to damage by endogenous and exogenous chemicals. Damaged mtDNA molecules are counteracted by the redundancy, repair, and degradation of mtDNA. In response to difficult-to-repair or excessive amounts of DNA lesions, mtDNA degradation is a crucial mitochondrial genome maintenance mechanism. Nevertheless, the molecular basis of mtDNA degradation remains incompletely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Both AP sites and fU are abundant DNA modifications that occur in the genome at comparable rates ( 46 ). Due to their aldehyde nature, they are prone to reactions with nucleophiles; however, until recently, the main reactivity of AP sites was considered to be due to the reversible formation of Schiff bases with lysine residues of proteins ( 21–23 ). Only recently other types of AP site reactivity were discovered, namely the formation of thiazolidines ( 19 , 20 ) and S -glycosylic derivatives ( 17 , 18 ) upon reaction with cysteine residues, as well as nucleophilic addition of exocyclic amino groups of neighboring nucleobases leading to the formation of N -glycosylic DNA ICLs ( 9–14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both AP sites and fU are abundant DNA modifications that occur in the genome at comparable rates ( 46 ). Due to their aldehyde nature, they are prone to reactions with nucleophiles; however, until recently, the main reactivity of AP sites was considered to be due to the reversible formation of Schiff bases with lysine residues of proteins ( 21–23 ). Only recently other types of AP site reactivity were discovered, namely the formation of thiazolidines ( 19 , 20 ) and S -glycosylic derivatives ( 17 , 18 ) upon reaction with cysteine residues, as well as nucleophilic addition of exocyclic amino groups of neighboring nucleobases leading to the formation of N -glycosylic DNA ICLs ( 9–14 ).…”
Section: Discussionmentioning
confidence: 99%
“…This processing includes AP incision with abundant AP endonuclease (APE1) ‘5 to the lesion and the removal of the resulting 5’ deoxyribosephosphate (dRP) group by DNA polymerase γ [ 130 ]. Recent data suggest that TFAM stimulates the incision of AP sites in mtDNA, reducing their half-life by 2–3 orders of magnitude to minutes, thus promoting their repair [ 131 , 132 , 133 , 134 , 135 ]. Earlier studies revealed preferential TFAM binding to DNA containing oxidatively damaged bases [ 136 ] and to DNA 4-way junctions [ 137 ], but surprisingly, not AP sites [ 136 ].…”
Section: Tfam and Mtdna Repairmentioning
confidence: 99%